Oxidative cell death in the central nervous system: mechanisms and therapeutic strategies - Liu, Nan; Liu, Ya; Wang, Yingzhao; Feng, Chunsheng; Piao, Meihua; Liu, Ming (Frontiers in Cell and Developmental Biology, 2025)
Oxidative cell death is caused by an overproduction of reactive oxygen species and an imbalance in the antioxidant defense system, leading to neuronal dysfunction and death. The harm of oxidative stress in the central nervous system (CNS) is extensive and complex, involving a variety of molecular and cellular level changes that may lead to a variety of acute and chronic brain pathologies, such as stroke, traumatic brain injury, or neurodegenerative diseases and psychological disorders. This review provides an in-depth look at the mechanisms of oxidative cell death in the central nervous system diseases. In addition, the review evaluated existing treatment strategies, including antioxidant therapy, gene therapy, and pharmacological interventions targeting specific signaling pathways, all aimed at alleviating oxidative stress and protecting nerve cells. We also discuss current advances and challenges in clinical trials, and suggest new directions for future research, including biomarker discovery, identification of potential drug targets, and exploration of new therapeutic techniques, with a view to providing more effective strategies for the treatment of CNS diseases.